MINAT BELI HAND PHONE Smartfren PADA MAHASISWA POLITEKNIK NEGERI SEMARANG - Rustono - Rustono (Politeknik Negeri Semarang, 2015)
The phenomenon of the increasing number ofSmartphone users at Andromax brand in thecommunity is lower, middle, and uppersegment. It seems that this smartphone growthis increasing in accordance with the needs ofthe community in communication to gainquick and easy by data services. Manyoperators compete in branding special mobilephone with sophisticated specification.Smartfren has recognized this opportunitysince 2011 and 2012 and consistent in dataservices and bundling which turned out to bebooming at this time (Ibrahim , Djoko Tata :2014) .A number of smartphone vendors do not dareto focus their work on secondary city, but forSmartfren, the city became the main target inmarketing Andromax. Seeing thisphenomenon the researchers are interested toAnalyze the Effect of Perceived Prices ,Brands, and Packaging of Smartfrenhandphone towards Buying ConsumerInterests In Semarang State PolytechnicStudents. Therefore, the problem of theproposed research is to determine the factorsthat most influence on buying interest onSmartfren hand phone .Further variables and indicators have beendetermined according to the study. A modelhas been developed and three hypotheseshave been formulated to address the problemof this research. The sampling technique waspurposive sampling method, while therespondents in this study amount to 77people. The respondents are mobile phoneusers of Smartfren among Semarang StatePolytechnic students. The research wascarried out for 4 months by distributingquestionnaires to the 77 respondents .The survey was conducted and analyzed usingValidity, Reliablitas then analyzed byRegression Analysis Tool to determine whichvariables most affect buying Interests. Thisstudy examines four objectives, i.e 1). Toanalyze how much influence the price is onthe buying Interests on Smartfren handphone,2). To analyze how much influence the Brandis on handphone Smartfren Buying interest,3). To analyze how much influence thepackaging is on the buying interest onSmartfren handphone. 4). To analyze whichvariables that most influence on Smartfrenhandphone buying interest.The finding is this research is the mostinfluential variable on buying interest onSmartfren handphone with equation BUYINGINTEREST RATES = 1.36 + 0.14 PRICE+0.62 BRAND + 0.33 BRAND PACKAGING +ε .